Effect of seawater on the properties of Epoxy Modified Concrete - Jupiter, T.; Hj Rashidi, A.; Ismail, I. (Universiti Malaysia Sarawak, (UNIMAS), 2010)
Epoxy is the most common type of polymer used by civil engineers to produce Polymer Cement Concrete (PCC). In this study, the effect of seawater on epoxy modified mortar in the Malaysian seawater is investigated using PCC mixes with Epoxy is used as the cement replacement. Fifteen 100x100x100 mm standard cubes were casted from five different mixes. The sample range from 5% to 50% epoxy replacement to cement content by weight ratio.